2021
DOI: 10.1007/s00439-021-02261-8
|View full text |Cite
|
Sign up to set email alerts
|

Canine DVL2 variant contributes to brachycephalic phenotype and caudal vertebral anomalies

Abstract: A frameshift deletion variant in the Wnt pathway gene dishevelled 2 (DVL2) is associated with a truncated, kinked tail (“screw tail”) in English Bulldogs, French Bulldogs and Boston Terriers. These breeds are also characterized by distinctive morphological traits, including a wide head, flat face and short-limbed dwarfism, which are characteristic of Robinow syndrome in humans, caused by defects in genes such as DVL1 and DVL3. Based on these phenotypic and genetic similarities, it has previously been hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…There are a few research articles that talk about genetic health issues in dogs, one of these conditions being brachycephaly. In [6] and [5] some of the genes in which mutations are connected with brachycephaly are discussed. In our paper we will consider one of these, the DVL2 gene, for which a genetic primer subsequence is presented in [5].…”
Section: Methodsmentioning
confidence: 99%
“…There are a few research articles that talk about genetic health issues in dogs, one of these conditions being brachycephaly. In [6] and [5] some of the genes in which mutations are connected with brachycephaly are discussed. In our paper we will consider one of these, the DVL2 gene, for which a genetic primer subsequence is presented in [5].…”
Section: Methodsmentioning
confidence: 99%
“…The authors also suggest that the derived DVL2 variant may contribute to the extreme brachycephaly seen in the French Bulldog, English Bulldog, and Boston Terrier (Mansour et al, 2018). Recent analysis by the authors of breeds with allele variation at the DVL2 marker confirm this hypothesis (Niskanen et al, 2021). The use of DVL2 as a genetic marker could be somewhat difficult to interpret.…”
Section: Tail Morphology Genetic Variantsmentioning
confidence: 96%
“…However, the SMOC2 ‐derived variant cannot reliably be used to predict skull shape as it only accounts for 36% of skull shape variation among domestic dog breeds (Marchant et al, 2017). Conversely, the DVL2 derived variant is thought to decrease hard palate length in a dose‐dependent manner, decrease skull base length in homozygous individuals, decrease the ratio of hard palate to skull base length similarly in homozygous and heterozygous individuals and increase the facial index of homozygous individuals (Niskanen et al, 2021). These features of the skull all contribute to the brachycephalic phenotype (Niskanen et al, 2021).…”
Section: Future Challenges and Opportunities For Canine Breed Classif...mentioning
confidence: 99%
“…We were very fortunate to have received several submissions from the prolific canine research laboratory of Hannes Lohi (Niskanen et al 2021;Kyöstilä et al 2021;Kaukonen et al 2021;Hytönen et al 2021a,b). In the first paper, Niskanen et al (2021) investigated the known variant in DVL2 associated with kinked tails and brachycephaly in bulldog breeds in an additional 1954 dogs from 15 breeds.…”
Section: Novel Findings Identified For Inherited Diseases In Dogsmentioning
confidence: 99%
“…We were very fortunate to have received several submissions from the prolific canine research laboratory of Hannes Lohi (Niskanen et al 2021;Kyöstilä et al 2021;Kaukonen et al 2021;Hytönen et al 2021a,b). In the first paper, Niskanen et al (2021) investigated the known variant in DVL2 associated with kinked tails and brachycephaly in bulldog breeds in an additional 1954 dogs from 15 breeds. The researchers confirmed that this deletion variant is associated with caudal vertebral malformations and brachycephaly, and may be involved with brachycephalic obstructive airways and congenital heart defects.…”
Section: Novel Findings Identified For Inherited Diseases In Dogsmentioning
confidence: 99%